Martin Luther King Jr : the life of a civil rights leader - Jeffrey, Gary.; Forsey, Christopher (New York : Rosen, 2007)
Presents a brief profile of civil rights leader Martin Luther King, Jr., written in graphic comic format, and describes his influence in improving the lives of African-Americans in the South.
Includes bibliographical references (p. 47) and index.
5.6
5-8
Keywords: King, Martin Luther, -- Jr., -- 1929-1968 -- Comic books, strips, etc. -- Juvenile literature; King, Martin Luther, -- Jr., -- 1929-1968 -- Cartoons and comics; King, Martin Luther, -- Jr., -- 1929-1968 -- Comic books, strips, etc; African Americans -- Comic books, strips, etc. -- Juvenile literature; African Americans -- Civil rights -- History -- 20th century -- Comic books, strips, etc. -- Juvenile literature; Baptists -- United States -- Clergy -- Comic books, strips, etc. -- Juvenile literature; Civil rights workers -- United States -- Comic books, strips, etc. -- Juvenile literature; African Americans -- Cartoons and comics; Cartoons and comics; Civil rights workers -- Cartoons and comics; Clergy -- Cartoons and comics; African Americans -- Comic books, strips, etc; Civil rights workers -- Comic books, strips, etc; Clergy -- United States -- Comic books, strips, etc; Comic books, strips, etc